Protective effects of α‐bisabolol on altered hemodynamics, lipid peroxidation, and nonenzymatic antioxidants in isoproterenol‐induced myocardial infarction: In vivo and in vitro evidences. Issue 10 (8th August 2018) - Meeran, Mohamed Fizur Nagoor; Laham, Farah; Al‐Taee, Hasan; Azimullah, Sheikh; Ojha, Shreesh
Abstract: The effect of α‐bisabolol on hemodyanimcs, lipid peroxidation, and nonenzymatic antioxidants was evaluated in isoproterenol‐induced myocardial infarction in rats. They were pre‐ and cotreated with α‐bisabolol (25 mg/kg body weight) daily for 10 days along with the subcutaneous injection of isoproterenol (85 mg/kg body weight) at an interval of 24 hours for 2 days (9th and 10th days). Increased activities of serum creatine kinase and creatine kinase‐MB along with altered levels/concentrations of lipid peroxidation products and nonenzymatic status were observed in the plasma and heart tissues of rats. Treatment with α‐bisabolol showed protective effects by reversing the altered biochemical parameters and hemodynamics studied. The in vitro reducing power of α‐bisabolol confirmed its potent antioxidant action. These biochemical benefits were translated into functional recovery by the maintenance of the hemodynamics in rats. The findings showed that α‐bisabolol has the potential to protect against isoproterenol‐induced myocardial infarction due to its potent antilipid peroxidation and antioxidant properties.